Design, manufacture and test of seismic shear (transverse) wave’s source for engineering purposes - M.M. Ahmed (Engineering and Technology Journal, 2017)
This research finds touches to the design and manufacture of generating seismic shear (transverse) waves polarized source system. The system consists of a source of surface horizontal movement (horizontal traction source) using a piece of wood (wooden plank). A series of field tests were conducting in order to demonstrate the efficiency of the system and the quality of the generated seismic shear wave. Through the obtained recordings and the quality of the received waves and its directional characteristics, which clearly show the system's success in achieving the aim of this study .In addition to the importance of the shear wave velocities in computing the elastic modulus to be used for engineering purposes of any intended projects.